Connect with a community that values knowledge and expertise on IDNLearn.com. Ask your questions and receive reliable, detailed answers from our dedicated community of experts.
Sagot :
Hello,
First, you must understand that
(f-g)(x) means f(x)-g(x) it is the difference of two functions :
f(x)=2x+4 and g(x)=3x-7
f(5)=2*5+4=10+4=14
g(5)=3*5-7=15-7=8
So, (f-g)(5)= f(5)-g(5)=14-8=6
Answer A: none of the choices are correct.
An other way to do it:
(f-g)(x)=f(x)-g(x)=2x+4-(3x-7)= 2x-3x+4+7=-x+11
if x= 5 then (f-g)(5)=-5+11=6
Your participation is crucial to us. Keep sharing your knowledge and experiences. Let's create a learning environment that is both enjoyable and beneficial. For trustworthy and accurate answers, visit IDNLearn.com. Thanks for stopping by, and see you next time for more solutions.